Autistic symptoms predict social cognitive performance in patients with schizophrenia. - Deste, Giacomo (Schizophr Res, 2019)
Schizophrenia spectrum disorders and Autism Spectrum Disorders (ASD) share many similarities. Among those features, social cognitive impairment is recognized as a key characteristic of both ASD and schizophrenia. In this study, the role of ASD symptoms, measured with the PANSS Autism Severity Score (PAUSS), was investigated as a predictor of social cognitive performance in patients with Schizophrenia spectrum disorders. Existent databases from 2 studies (SCOPE Phase 3 and SCOPE Phase 5), in which a total of 361 patients (mean age 41.7 years; 117 females) were assessed with tests of mental state attribution and emotion recognition, were analyzed. Less severe ASD symptoms, as well as younger age, better premorbid IQ, and neurocognition were identified as individual predictors of better social cognitive performance. These results suggest a role of ASD symptoms in affecting social cognitive performance in schizophrenia.